Prophetic dialogue: reflections on Christian mission today - Bevans, Stephen B. (Orbis Books, 2011)
The mission has a church: an invitation to the dance -- "We were gentle among you": Christian mission as dialogue -- "I am not ashamed of the Gospel": mission as prophecy -- Mission for the church in the twenty first century: prophetic dialogue and contextual theology -- Unraveling a "complex reality": six elements of mission -- Entering someone else's garden: intercultural mission/ministry -- Letting go and speaking out: prophetic dialogue and the spirituality of inculturation -- Table fellowship: mission in the Areopagus of today -- A short history of the church's mission: prophetic dialogue through the ages -- Church teaching, mission, and prophetic dialogue: Ad gentes, Evangelii nuntiandi, Redemptoris missio, and dialogue and proclamation